Groundwater Suitability for Agriculture using GIS Techniques in the Lower Part of Lesser Zab River Basin - A.Al-Dabbas, Moutaz; Al-Shammari, Ayad A. (Iraqi Journal of Science, 2023)
Suitability of groundwater for irrigation depends upon many constrains factors, these factors depend upon the dissolved salts during the flow of the recharge of the groundwater beside the aquifer constituents itself, from these factors (EC, SO4-2, Cl-, Na%, and SAR) .The spatial distribution of each constrain factor may show discrepancy from the another, so it is not possible to depend upon one factor. The aim of this work is to present a classification of the groundwater quality for agriculture including all the mentioned five factors, by using Arc GIS which provides tools to serve a purpose to create conceptual model for solving spatial problems. A set of conceptual steps used to build a model for suitability map of groundwater for irrigation. 3D spatial analyst can interpolate the data of each constrain factor into raster. The rasters are reclassified by grouping ranges of values into single value. New output raster represents the value of the rasters after making weighted overlay and after calculating the influence of each constrain factor by using Analytical Hierarchy Process (AHP), the final raster shows spatial extent of groundwater quality and its suitability for agriculture. The lower part of Lesser Zab River Basin was chosen to know the suitability of groundwater for irrigation. The final raster shows that there are 4 classes (Excellent-Doubtful), the excellent suitability scattered in a small areas, while the good, permissible, and doubtful distributed on the most parts of the area.